2022
DOI: 10.1002/cam4.4432
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the quality of multidisciplinary team meetings: A narrative review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…3 The purpose of MDT meetings is to provide opportunities for health professionals with differing expertise to meet on a regular basis with the aim of generating treatment recommendations on the basis of best evidence while taking into consideration patient preference. 4 It has been demonstrated that MDT decisions lead to revisions of cancer diagnoses and treatment plans in new cancer cases, better adherence to evidence-based guidelines, improved consideration for inclusion in clinical trials, and more accurate staging and treatment selections resulting in increased survival rates. 1,3,5 MDTs may improve patient satisfaction and patient trust.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The purpose of MDT meetings is to provide opportunities for health professionals with differing expertise to meet on a regular basis with the aim of generating treatment recommendations on the basis of best evidence while taking into consideration patient preference. 4 It has been demonstrated that MDT decisions lead to revisions of cancer diagnoses and treatment plans in new cancer cases, better adherence to evidence-based guidelines, improved consideration for inclusion in clinical trials, and more accurate staging and treatment selections resulting in increased survival rates. 1,3,5 MDTs may improve patient satisfaction and patient trust.…”
Section: Introductionmentioning
confidence: 99%
“…1 The ability to implement clinical decisions and the effective care coordination by the multiteam affects quality of MDT working. 4,9-13…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations